Between law and narrative the method and function of abstraction - Lee, Bernon (Piscataway, NJ Gorgias Press, 2010)
This book proposes that certain passages of law in Leviticus and Numbers offer direction for the interpretation of adjacent segments of narrative
Includes bibliographical references (pages 297-308) and index
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Bible -- Criticism, Narrative; Bible -- Criticism, Narrative; Law (Theology) -- Biblical teaching; Jewish Law -- Interpretation and construction; Hochschulschrift